2010
DOI: 10.1016/j.jal.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatizing hybrid logic using modal logic

Abstract: We study hybrid logics with nominals and 'actuality' operators @ i . We recall the method of ten Cate, Marx, and Viana to simulate hybrid logic using modalities and 'nice' frames, and we show that the hybrid logic of a class of frames is the modal logic of the class of its corresponding nice frames. We also extend this definition to 'fairly nice frames', to capture their closure under disjoint union. Using these results, we show how to axiomatize the hybrid logic of any elementary class of frames. Then we stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In [27], Blackburn and ten Cate approach several extensions of basic hybrid logic, and provide them with Hilbert axiomatizations. Also, Ian Hodkinson's work on axiomatizing hybrid logics using modal logics is quite interesting [62]. And finally, Torben Braüner worked on defining first-order hybrid logic [32], intuitionistic hybrid logic [33] and many-valued hybrid logic [60].…”
Section: History Of Hybrid Logicsmentioning
confidence: 99%
“…In [27], Blackburn and ten Cate approach several extensions of basic hybrid logic, and provide them with Hilbert axiomatizations. Also, Ian Hodkinson's work on axiomatizing hybrid logics using modal logics is quite interesting [62]. And finally, Torben Braüner worked on defining first-order hybrid logic [32], intuitionistic hybrid logic [33] and many-valued hybrid logic [60].…”
Section: History Of Hybrid Logicsmentioning
confidence: 99%
“…Correspondence and completeness theory for hybrid logic Existing literature on correspondence and completeness theory for hybrid logic is abundant, see [1,4,6,10,11,12,13,14,18,20,22]. Gargov and Goranko proved that any extension of K H with pure axioms (formulas that contain nominals only but no propositional variables) is strongly complete.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondence Theory for Hybrid Logic In the literature, there are many existing works on the correspondence theory for hybrid logic [1,3,6,11,12,13,14,15,18,19]. In particular, ten Cate et al [19] showed that any hybrid logic obtained by adding modal Sahlqvist formulas to the basic hybrid logic H is strongly complete.…”
Section: Introductionmentioning
confidence: 99%